PEMBUATAN STANDARD OPERATING PROCEDURE PENGEMBANGAN SISTEM INFORMASI MANAJEMEN: STUDI KASUS DPTSI ITS - Herdiyanti, Anisah; Puspitaningrum, Ari Cahaya; Astuti, Hanim Maria; Yuhana, Umi Laili (SISFO, 2018)
DPTSI is an information technology unit in Institut Teknologi Sepuluh Nopember (ITS). One of its section is Subdit PSI who is responsible for developing Management Information Systems (MIS) application to other units in ITS. Some problems exist when there is no single procedure available, including unstandardized processes of software development and lack of control in software quality development. A standard operating procedure is needed for this purpose and is constructed according to IT governance best practice framework, i.e. ITIL v3 and COBIT 5. Prior the development of SOP, a gap analysis was conducted to find important activities in software development. As a result, 5 (five) SOPs and 14 forms were developed. The results were then validated through simulation and focus group discussion with Subdit PSI. The research contributes to the implementation of IT governance best practice framework and also serves as a reference for management to standardize IT management process.